A randomised cross-over study assessing the “blue pyjama syndrome” in major depressive episode - Hélèna Delmas (Nature Portfolio, 2017)
Abstract This paper introduces a “blue pyjama syndrome” (whereby wearing hospital pyjamas results in an exaggerated impression of severity). We performed a 5-day, prospective, randomized, cross-over study in a French mood disorder unit for inpatients. At Day 1 (D1) and Day 5 (D5), two 5-minute video interviews were recorded with patients in pyjamas or in day clothes (the sequence was randomly allocated). Psychiatrists unaware of the study objective assessed the videos and scored their clinical global impressions (CGI, with scores ranging from 1 to 7). Of 30 participants with major depressive episode selected for inclusion, 26 participants (69% women) provided useable data for an evaluation by 10 psychiatrists. Pyjamas significantly increased the psychiatrists’ CGI ratings of disease severity by 0·65 [0·27; 1·02] points. The psychiatrists’ global impressions also rated patients as significantly less severe at D5 in comparison with D1 by −0·66 [−1·03; −0·29] points. The “blue pyjama syndrome” is in the same order of magnitude as the difference observed after a week of hospitalisation. This potentially calls into question the reliability and validity of observer ratings of depression.